Recombinant Human Proteoglycan 4 Regulates Phagocytic Activation of Monocytes and Reduces IL-1β Secretion by Urate Crystal Stimulated Gout PBMCs - ElSayed, Sandy; Jay, Gregory D.; Cabezas, Ralph; Qadri, Marwa; Schmidt, Tannin A.; Elsaid, Khaled A. (Frontiers in Immunology, 2021)
Objectives To compare phagocytic activities of monocytes in peripheral blood mononuclear cells (PBMCs) from acute gout patients and normal subjects, examine monosodium urate monohydrate (MSU) crystal-induced IL-1β secretion ± recombinant human proteoglycan 4 (rhPRG4) or interleukin-1 receptor antagonist (IL-1RA), and study the anti-inflammatory mechanism of rhPRG4 in MSU stimulated monocytes. Methods Acute gout PBMCs were collected from patients in the Emergency Department and normal PBMCs were obtained from a commercial source. Monocytes in PBMCs were identified by flow cytometry. PBMCs were primed with Pam3CSK4 (1μg/mL) for 24h and phagocytic activation of monocytes was determined using fluorescently labeled latex beads. MSU (200μg/mL) stimulated IL-1β secretion was determined by ELISA. Reactive oxygen species (ROS) generation in monocytes was determined fluorometrically. PBMCs were incubated with IL-1RA (250ng/mL) or rhPRG4 (200μg/mL) and bead phagocytosis by monocytes was determined. THP-1 monocytes were treated with MSU crystals ± rhPRG4 and cellular levels of NLRP3 protein, pro-IL-1β, secreted IL-1β, and activities of caspase-1 and protein phosphatase-2A (PP2A) were quantified. The peritoneal influx of inflammatory and anti-inflammatory monocytes and neutrophils in Prg4 deficient mice was studied and the impact of rhPRG4 on immune cell trafficking was assessed. Results Enhanced phagocytic activation of gout monocytes under basal conditions (p<0.001) was associated with ROS generation and MSU stimulated IL-1β secretion (p<0.05). rhPRG4 reduced bead phagocytosis by normal and gout monocytes compared to IL-1RA and both treatments were efficacious in reducing IL-1β secretion (p<0.05). rhPRG4 reduced pro-IL-1β content, caspase-1 activity, conversion of pro-IL-1β to mature IL-1β and restored PP2A activity in monocytes (p<0.05). PP2A inhibition reversed rhPRG4’s effects on pro-IL-1β and mature IL-1β in MSU stimulated monocytes. Neutrophils accumulated in peritoneal cavities of Prg4 deficient mice (p<0.01) and rhPRG4 treatment reduced neutrophil accumulation and enhanced anti-inflammatory monocyte influx (p<0.05). Conclusions MSU phagocytosis was higher in gout monocytes resulting in higher ROS and IL-1β secretion. rhPRG4 reduced monocyte phagocytic activation to a greater extent than IL-1RA and reduced IL-1β secretion. The anti-inflammatory activity of rhPRG4 in monocytes is partially mediated by PP2A, and in vivo, PRG4 plays a role in regulating the trafficking of immune cells into the site of a gout flare.